First record of the genus Cisaris Townes (Ichneumonidae: Phygadeuontinae) from Vietnam, with descriptions of four new species - Pham, Nhi Thi; Cao, Nga Thi Quynh (Zootaxa, 2025)
The Darwin wasp genus Cisaris is recorded for the first time from Vietnam. Four new species are described on the basis of material from the country including C. carinatus sp. nov., C. robustus sp. nov., C. rugosus sp. nov., and C. tergalis sp. nov. The key to the world species of Cisaris by Sun & Sheng (2011) is modified to include four new species from Vietnam.